Socio-economic Impact of “Wheat Seed –Village” in Madhya Pradesh - Singh, A.K.; Pandey, H.N.; Saiprasad, S.V. (Indian Journal of Extension Education, 2010)
To improve productivity, availability of quality seed to the farmers must be ensured. Supply of quality seed in large quantity to farmers is only possible through a novel self-sustaining model such as “Seed Village”. This concept is bases on principle of quality seed production by the trained farmers in their own fields, for use of the farming community. Kusmania village of Kannaud Block in Dewas District of Madhya Pradesh was selected to demonstrate quality seed production through “Seed Village” by farmer participatory approach. Overall 15 demonstrations were conducted with limited irrigation varieties in 30.2 hectares area. Check variety Sujata was sown in 10 hectares area. Average grain yield (Q/ha) was 32 and 20 in test and check varieties respectively. Yield increase was 56% over check in these demonstrations. Employment generated (man-days per ha.) was 41 and 29 in test and check varieties respectively. Net return (Rs./ha.) was 34595 and 12846 for the test and check varieties respectively. Higher yields and better quality led to better profits in test varieties as compared to check varieties. New varieties have been proved better with respect to productivity, quality, profitability and employment generation. To improve wheat productivity farmers can produce process and sell seeds through cooperative efforts in the form of a seed village. Many qualitative changes were also witnessed due to impact of seed village.